O uso da bicicleta como instrumento em ensino de física - Araújo, Paulo Roberto Freitas (2021)
This work is aimed at high school teachers based on the content that must be presented to students during this period of their learning. The choice of the Product was due to the fact that I am a cyclist and have identified, on the bicycle, a huge range of subjects related to Physics. Another factor that influenced me was that, although we have School Transportation, many of the students travel to the School using the bicycle, a fact that happens because the School where I teach is one of the few existing in the place. After all, using the Product, the way the classes take place becomes something more pleasurable and close to the student's daily life.